2014
DOI: 10.1007/s00586-014-3330-y
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative blood transfusion does not decrease survival after surgical treatment of spinal metastases

Abstract: The results of the present study support that perioperative blood transfusion of <5 units does not decrease survival in patients operated for spinal metastases. Transfusion of 1-2 units seems to be associated with increased 12-month survival. Future studies should assess if a liberal transfusion regime can be applied to this group of patients; thereby, prioritizing early postoperative mobilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…On the other hand, some studies have refuted that blood transfusion did not increase the incidence of postoperative complications or infections . In patients undergoing MSTS, there have been studies in current literature that have evaluated the impact of ABT on survival with no emphasis on postoperative complications . With this background, we performed a retrospective analysis of the data of patients undergoing surgery for spinal metastases to explicate the influence of perioperative ABT on the spectrum of postoperative complications and infections.…”
mentioning
confidence: 99%
“…On the other hand, some studies have refuted that blood transfusion did not increase the incidence of postoperative complications or infections . In patients undergoing MSTS, there have been studies in current literature that have evaluated the impact of ABT on survival with no emphasis on postoperative complications . With this background, we performed a retrospective analysis of the data of patients undergoing surgery for spinal metastases to explicate the influence of perioperative ABT on the spectrum of postoperative complications and infections.…”
mentioning
confidence: 99%
“…To date, only two studies were identified in the literature in which survival was the only outcome measured in relation to blood transfusion in patients who underwent MSTS. Clausen and colleagues . retrospectively studied the survival of 170 patients with respect to blood transfusion, age, sex, preoperative Hb levels, Tokuhashi scores, and the number of instrumented levels.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, it has been postulated that immune suppression results in cancer recurrence or progression . Blood transfusion has also been proposed as an indicator of an overall poor outcome regardless of cancer recurrence and reportedly is associated with a poor prognosis in terms of all‐cause and cancer‐related mortality . However, some studies have reported that blood transfusion did not compromise oncological outcomes like cancer recurrence or survival .…”
mentioning
confidence: 99%
“…Clausen et al [7] showed that perioperative allogeneic blood transfusion in patients with spine metastases was not associated with 3-month survival; they found an increased 12-month survival after 1 to 2 units of allogeneic blood transfusion compared with no transfusion (odds ratio, 2.6; 95% CI, 1.0-6.8; p = 0.049) [7]. Increased survival might be explained by a difference in indication for blood transfusion or anatomic site studied, or because of the few confounding factors taken into account (preoperative hemoglobin, age, sex, Tokuhashi score [survival prognostication score], and number of instrumented levels) [7].…”
Section: Discussionmentioning
confidence: 99%
“…Clausen et al [7] showed that perioperative allogeneic blood transfusion in patients with spine metastases was not associated with 3-month survival; they found an increased 12-month survival after 1 to 2 units of allogeneic blood transfusion compared with no transfusion (odds ratio, 2.6; 95% CI, 1.0-6.8; p = 0.049) [7]. Increased survival might be explained by a difference in indication for blood transfusion or anatomic site studied, or because of the few confounding factors taken into account (preoperative hemoglobin, age, sex, Tokuhashi score [survival prognostication score], and number of instrumented levels) [7]. Previous studies in visceral metastatic disease have shown a negative effect of perioperative blood transfusion on survival [14,16]: Katoh et al [14] found that perioperative transfusion was independently associated with worse survival after resection of stage IV (disseminated disease) colorectal cancer (n = 162) after accounting for clinical and treatment parameters; Margulis et al [16] reported that survival of patients undergoing cytoreductive nephrectomy for metastatic renal cell carcinoma also was negatively influenced by intraoperative blood transfusion.…”
Section: Discussionmentioning
confidence: 99%